Novel NALCN variant: altered respiratory and circadian rhythm, anesthetic sensitivity. Issue 11 (11th October 2016) - Lozic, Bernarda; Johansson, Stefan; Lovric Kojundzic, Sanja; Markic, Josko; Knappskog, Per Morten; Hahn, Angelika F.; Boman, Helge
Abstract: The sodium leak channel, a Na + ‐permeable, nonselective cation channel, is widely expressed in the nervous system, contributing a basal Na + ‐leak conductance and regulating neuronal excitability. A 3‐year‐old girl, heterozygous for a de novo missense mutation in NALCN (c.956C>T; p.Ala319Val) predicted to be deleterious, presented from birth with: stimulus‐induced, episodic contractures of the limbs and face with associated respiratory distress; distal arthrogryposis; severe axial hypotonia; and severe global developmental delay (CLIFAHDD syndrome). In infancy, she manifested a reversed sleep‐wake rhythm, nocturnal life‐threatening respiratory rhythm disturbances with central apnea. Sevoflurane sensitivity caused respiratory depression and cardiac arrest.